Development of an Updated Global Land In Situ‐Based Data Set of Temperature and Precipitation Extremes: HadEX3. Issue 16 (19th August 2020) - Dunn, Robert J. H.; Alexander, Lisa V.; Donat, Markus G.; Zhang, Xuebin; Bador, Margot; Herold, Nicholas; Lippmann, Tanya; Allan, Rob; Aguilar, Enric; Barry, Abdoul Aziz; Brunet, Manola; Caesar, John; et al.
Abstract: We present the second update to a data set of gridded land‐based temperature and precipitation extremes indices: HadEX3. This consists of 17 temperature and 12 precipitation indices derived from daily, in situ observations and recommended by the World Meteorological Organization (WMO) Expert Team on Climate Change Detection and Indices (ETCCDI). These indices have been calculated at around 7, 000 locations for temperature and 17, 000 for precipitation. The annual (and monthly) indices have been interpolated on a 1.875°×1.25° longitude‐latitude grid, covering 1901–2018. We show changes in these indices by examining "global"‐average time series in comparison with previous observational data sets and also estimating the uncertainty resulting from the nonuniform distribution of meteorological stations. Both the short and long time scale behavior of HadEX3 agrees well with existing products. Changes in the temperature indices are widespread and consistent with global‐scale warming. The extremes related to daily minimum temperatures are changing faster than the maximum. Spatial changes in the linear trends of precipitation indices over 1950–2018 are less spatially coherent than those for temperature indices. Globally, there are more heavy precipitation events that are also more intense and contribute a greater fraction to the total. Some of the indices use a reference period for calculating exceedance thresholds. We present a comparison between using 1961–1990 and 1981–2010. The differences between the time series of the temperature indices observed over longer time scales are shown to be the result of the interaction of the reference period with a warming climate. The gridded netCDF files and, where possible, underlying station indices are available from www.metoffice.gov.uk/hadobs/hadex3 and www.climdex.org . Key Points: We present an updated data set of gridded temperature and precipitation extremes Spatio‐temporal coverage over 1901–2018 for 29 extremes indices was improved over previous version We find increased (decreased) intensity and frequency of warm (cool) extremes and increased intensity of heavy precipitation events